Peningkatan kemampuan pemecahan masalah matematika melalui Problem Based Learning Pada SIswa Kelas VI SDIT Insan Mulia Surakarta - Istiqomah, Nurul (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study is to improve students' mathematical problem solving skills by using a problem-based learning model. The method used in this study is classroom action research (PTK) which includes four stages, namely: planning, implementation, observation and reflection. The subjects of this study were grade VI students totaling 26 students. Data analysis uses qualitative and quantitative analysis. The results showed that problem-based learning models  can improve mathematical problem solving skills. The achievement of problem-solving ability indicators in cycle I increased in cycle II. The indicator  of students' ability to understand problems 81.01% increased to 89.74%, the percentage of students' ability to plan problem solving 77.77% increased to 84.62%,  the percentage of students' ability to carry out problem solving 69.65% increased to 77.35 and the percentage of students' ability to re-examine the procedure of solving results 67.30% increased to 75.64%. This study concluded that the implementation  of problem-based learning improves the mathematical problem solving ability of grade VI students of SDIT Insan Mulia Surakarta. The problem based learning model can  be used as an alternative to learning because it can improve students' mathematical problem solving skills.